Cashew Nut Shell Liquid A Goldfield for Functional Materials - Anilkumar, Parambath; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book highlights and reviews the renewable feed stock principle of green nanotechnology by focusing the use of plant-derived cardanol as a renewable starting material for the synthesis of advanced materials. The book presents the chemistry of cardanol and methods of isolation, covers macro and nano structures based on cardanol as well as potential applications of such materials. Future perspectives on cardanol based green nanotechnology are highlighted in the final chapter.
Preface -- Methods of Isolation and Chemistry of Cardanol -- Cardanol Derived Surfactants and Their Nanomicelles -- Cardanol Based High Performance Macromolecules -- Cardanol Based Self-assembled Nanostructures -- Cardanol Derived Nano-templates -- Cardanol Metal Nano-hybrid Assemblies -- Cardanol Based Liquid Crystals and NLO materials -- Cardanol Based Materials in Nanomedicine -- Industrial Applications of Cardanol Derived Materials -- Future Perspectives on Cardanol Based Green Nanotechnology -- Subject Index.
Keywords: Nanotechnology; Renewable energy sources; Ceramic materials; Nanochemistry; Nanotechnology; Renewable Energy; Ceramics; Nanochemistry